KUALITAS PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN KONSUMEN MEMBELI AIR MINERAL AQUA - Deviana, Iga Maghfirah (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2018)
This research aims to know and analyze: (1) the influence of product quality and brand image to consumer's decision to buy AQUA brand mineral water at Faculty of Economics in Tadulako This research aims to: 1) determine and analyze simultaneous influence of product quality and brand image on consumers? decision to buy AQUA brand mineral water in The Faculty of Economics of Tadulako University; (2) determine and analyze the influence of product quality on consumers? decision to buy AQUA brand mineral water in The Faculty of Economics of Tadulako University;(3)determine and analyze the influence of brand image on consumers? decision to buy AQUA brand mineral water in The Faculty of Economics of Tadulako University. The type of research is quantitative. The Population consists of students in The Faculty of Economics who bought AQUA brand mineral water. Sampling technique is purposive to select 100 respondents. Data collection is questionnaires. Method of analysis is multiple linear regressions. The result indicates that: (1) product quality and brand image simultaneously influence consumer's decision to buy AQUA brand mineral water in The Faculty of Economics of Tadulako University; (2) product quality has partial influence on consumer decision to buy AQUA brand mineral water in The Faculty of Economics of Tadulako University; (3) brand image has partial influence on consumer decision to buy mineral water of AQUA brand in Faculty of Economics of Tadulako University.